DO FIRM CHARACTERISTICS MATTER IN EXPLAINING THE LAPSE RATE OF LIFE INSURANCE POLICIES AND FAMILY TAKAFUL CERTIFICATES IN MALAYSIA? - Farah Adibah Dato’ Zaihan; Tuck Cheong Tang (The International Journal of Banking and Finance)
This study discovers the influence of the firm’s characteristics (i.e. firm size, firm leverage, aggressiveness of sales, board of directors’ size and diversity) on the lapse rate of life insurance policies and family takaful certificates in Malaysia. The panel data includes 25 insurance operators consisting of 14 conventional insurers and 11 takaful operators available between 2014 and 2022.The cross-sectional Ordinary Least Square (OLS) estimates show that firm size has a negative influence on lapse rates of life insurance (2019-2021), while a positive sign for firm leverage (2017, 2020 and 2021). The aggressiveness of sales shows the inconsistent influence on the lapse rate of life insurance in 2017 (positive) and in 2021 (negative). The firm leverage negatively influences on the lapse rate of family takaful for 2017 and 2018. The panel data estimates show that firm leverage and diversity of the firm’s board of directors significantly impact the life insurance lapse rate while only firm diversity significantly impacts family takaful lapse rates. This study offers policy implications for the insurance industry in Malaysia, especially by the Bank Negara Malaysia (BNM).